Infrared Thermography Application in Buildings Diagnosis: A Proposal for Test Procedures - Eva Barreira (2013)
The study of hygrothermal behaviour is essential to evaluate the performance of construction components and building envelopes. Most building pathologies are related with temperature action. The use of non-destructive techniques to evaluate a building behaviour may be very useful as there is no need to destroy the building components, which would interfere with the users life. Infrared thermography is a non-destructive testing technology that can be applied to determine the surface temperature of objects. This technology has been applied to buildings for a couple of decades, to evaluate the building performance. It has been used to detect insulation defects, air leakages, heat losses through windows, moisture and different hidden details. This work evaluates the applicability of thermography to study the behaviour of building materials and building envelopes. A short literature review about thermography principles is presented. It is also showed the effect on the results of some factors that affect infrared thermography measurements. Several applications of infrared thermography to building diagnosis are listed, based on the work published by the scientific community. And finally, three test procedures are described in detailed to detect detachments on wall renderings, to evaluate the thermal comfort of floor coatings and to analyse the wetting and drying processes. (c) 2013, Springer-Verlag Berlin Heidelberg.